(untitled) (Tempo e Argumento, 2021)
Historical facts are expressed in the topographic space of cities, where past memory covers are overlapped and condensed over time. Although permeated with marks, the spaces of cities often become emptied of their social, historical and political meaning due to the fast pace of everyday life. It is noticed that between the establishment of memorial public policies aimed at the celebration and tribute, and the dissemination of content and historical knowledge that results in an awareness of the subjects who circulate in the memory spaces there is a distance that needs to be carefully discussed. In this text we seek to analyze the choice, preservation and management of memory spaces related to the latest military dictatorships in Latin America, and the challenge of “giving historical meaning” to these spaces from the perspective of human rights